Evaluation of the Pancasila Student Profile Strengthening Project Program at Public Middle Schools in Badung Regency - Purnamasari, I Gusti Dian Ayu; Dantes, Kadek Rihendra; Yudana, I Made (Journal of Science and Education (JSE), 2025)
This study aims to evaluate the implementation of the Pancasila Student Profile Enhancement Project program at SMP Negeri Badung Regency, a case study of SMP Negeri 4 Abiansemal. This study is an evaluative study with a quantitative descriptive approach using the CIPP method (context, input, process and product). The population of this study was the P5 Project Team (Principal, School Treasurer and project implementing teachers) of class VIII totaling 18 people, and class VIII students of SMP Negeri 4 Abiansemal in the 2024-2025 academic year totaling 235 people. The research sample was a saturated sample for the project team totaling 18 people and 148 students determined by the simple random sampling method. The data collection techniques used were interviews to obtain initial information regarding the implementation of P5, questionnaires as the main data source, and observations to strengthen the results of the questionnaire. The questionnaire was compiled using a Likert scale (1-5). Data analysis was carried out on the CIPP variables using the direction of the T value of each variable to determine the effectiveness of the program. The results of this study are the effectiveness of the P5 program from the contact aspect obtained positive (+) or effective results. The input aspect obtained positive (+) or effective results, the process aspect obtained positive (+) or effective results, and the product aspect obtained negative (-) or ineffective results.